Organization of physical preparation in the organs of internal affairs of Ukraine: psychological aspect - Alekseenko A.O (Kharkov National Pedagogical University, 2010)
The system of special physical preparation is examined in the organs of internal affairs of Ukraine. The psychological sides of professional activity of workers of militia are taken into account. Structurally forming influence of facilities of the special physical preparation is offered on psychologically important qualities of workers of militia. Recommendations are presented on introduction in the educational process of methods of forming psychological readiness of workers of militia to implementation of the official duties.